Evaluasi Budaya Kerja sebagai Faktor Penentu Kinerja Sekolah: Kajian Literatur pada Jenjang SMP Sederajat - Abdul Qadir Jaelani; Mardiana Istilam (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to evaluate the role of work culture as a determining factor of school performance at the junior secondary school (SMP equivalent) level through a literature review approach. The research method employed was library research using a qualitative-descriptive approach, analyzing national and international journal articles as well as academic books published between 2020 and 2024. Data analysis was conducted using content analysis techniques with thematic synthesis to identify patterns, trends, and key findings related to the relationship between work culture and school performance. The results of the review indicate that a strong, positive, and consistently internalized work culture contributes significantly to improving teacher performance, school managerial effectiveness, and the quality of educational services. Furthermore, principal leadership and organizational climate serve as reinforcing factors in the formation and development of work culture. These findings emphasize that work culture is a strategic element that cannot be separated from efforts to enhance school performance, particularly at the junior secondary school level, which has its own characteristics and challenges.